Arm Span and Ulnar Length Are Reliable and Accurate Estimates of Recumbent Length and Height in a Multiethnic Population of Infants and Children under 6 Years of Age. Issue 9 (16th July 2014) - Forman, Michele R.; Zhu, Yeyi; Hernandez, Ladia M.; Himes, John H.; Dong, Yongquan; Danish, Robert K.; James, Kyla E.; Caulfield, Laura E.; Kerver, Jean M.; Arab, Lenore; Voss, Paula; Hale, Daniel E.; et al.
Abstract: Surrogate measures are needed when recumbent length or height is unobtainable or unreliable. Arm span has been used as a surrogate but is not feasible in children with shoulder or arm contractures. Ulnar length is not usually impaired by joint deformities, yet its utility as a surrogate has not been adequately studied. In this cross-sectional study, we aimed to examine the accuracy and reliability of ulnar length measured by different tools as a surrogate measure of recumbent length and height. Anthropometrics [recumbent length, height, arm span, and ulnar length by caliper (ULC), ruler (ULR), and grid (ULG)] were measured in 1479 healthy infants and children aged <6 y across 8 study centers in the United States. Multivariate mixed-effects linear regression models for recumbent length and height were developed by using ulnar length and arm span as surrogate measures. The agreement between the measured length or height and the predicted values by ULC, ULR, ULG, and arm span were examined by Bland-Altman plots. All 3 measures of ulnar length and arm span were highly correlated with length and height. The degree of precision of prediction equations for length by ULC, ULR, and ULG ( R 2 = 0.95, 0.95, and 0.92, respectively) was comparable with that by arm span ( R 2 = 0.97) using age, sex, and ethnicity as covariates; however, height prediction by ULC ( R 2 = 0.87), ULR ( R 2 = 0.85), and ULG ( R 2 = 0.88) was less comparable with arm span ( R 2 = 0.94). Our study demonstrates that arm span and ULC, ULR, or ULG can serve as accurate and reliable surrogate measures of recumbent length and height in healthy children; however, ULC, ULR, and ULG tend to slightly overestimate length and height in young infants and children. Further testing of ulnar length as a surrogate is warranted in physically impaired or nonambulatory children.